560G>A (rs4986782) (R187Q) Single Nucleotide Polymorphism in Arylamine N-Acetyltransferase 1 Increases Affinity for the Aromatic Amine Carcinogens 4-Aminobiphenyl and N-Hydroxy-4-Aminobiphenyl: Implications for Cancer Risk Assessment - Doll, Mark A.; Hein, David W. (Frontiers in Pharmacology, 2022)
Human arylamine N-acetyltransferase 1 (NAT1) catalyzes the N-acetylation of arylamine carcinogens such as 4-aminobiphenyl (ABP), and following N-hydroxylation, the O-acetylation of N-hydroxy-arylamine carcinogens such as N-hydroxy-ABP (N-OH-ABP). Genetic polymorphisms in NAT1 are linked to cancer susceptibility following exposures. The effects of individual single nucleotide polymorphisms (SNPs) in the NAT1 coding exon on Michaelis-Menten kinetic constants was assessed for ABP N-acetyltransferase and N-OH-ABP O-acetyltransferase activity following transfection of human NAT1 into COS-1 cells (SV40-transformed African green monkey kidney cells). NAT1 coding region SNPs 97C>T (rs56318881) (R33stop), 190C>T (rs56379106) (R64W), 559C>T (rs5030839) (R187stop) and 752A>T (rs56172717) (D251V) reduced ABP N- acetyltransferase and N-OH-ABP O-acetyltransferase activity below detection. 21T>G (rs4986992) (synonymous), 402T>C (rs146727732) (synonymous), 445G>A (rs4987076) (V149I), 613A>G (rs72554609) (M205V) and 640T>G (rs4986783) (S241A) did not significantly affect Vmax for ABP N-acetyltransferase or N-OH-ABP O-acetyltransferase. 781G>A (rs72554610) (E261K), and 787A>G (rs72554611) (I263V) slightly reduced ABP N-acetyltransferase and N-OH-ABP O-acetyltransferase activities whereas 560G>A (rs4986782) (R187Q) substantially and significantly reduced them. 560G>A (rs4986782) (R187Q) significantly reduced the apparent Km for ABP and N-OH-ABP a finding that was not observed with any of the other NAT1 SNPs tested. These findings suggest that the role of the 560G>A (rs4986782) (R187Q) SNP cancer risk assessment may be modified by exposure level to aromatic amine carcinogens such as ABP.